The Dandy-Walker syndrome - Domingo, Zayne (Division of Neurosurgery, 2023)
The Dandy-Walker syndrome (DWS) has been defined as a congenital malformation of the structures of the posterior fossa characterised by cystic dilatation of the fourth ventricle, hypoplasia of the cerebellar vermis, enlargement of the posterior fossa, atresia of the foramina of Luschke and Magendie and associated hydrocephalus. Since its initial description definitions have been modified to include findings encountered in a particular case or series of cases. This lack of uniformity of the diagnostic criteria has made the objective assessment of management and outcome difficult. It has also resulted in terms such as DandyWalker variant, mega cisterna pouch and prominent cisterna posterior fossa cysts which magna, magna, do not persistent Blake's being applied to fit in with the particular criteria used for the series described.